2018
DOI: 10.3171/2017.10.focus17563
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative depression, lumbar fusion, and opioid use: an assessment of postoperative prescription, quality, and economic outcomes

Abstract: OBJECTIVEPreoperative depression has been linked to a variety of adverse outcomes following lumbar fusion, including increased pain, disability, and 30-day readmission rates. The goal of the present study was to determine whether preoperative depression is associated with increased narcotic use following lumbar fusion. Moreover, the authors examined the association between preoperative depression and a variety of secondary quality indicator and economic outcomes, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 34 publications
(31 reference statements)
3
52
1
Order By: Relevance
“…Temporal and regional trends were analyzed by logistic regression for binary outcomes and linear regression for continuous variables, controlling for age and sex. For determining risk factors for chronic opioid use, univariate logistic regression was performed on variables of interest in-accordance with previous studies in the literature [24]. Factors that were significant…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temporal and regional trends were analyzed by logistic regression for binary outcomes and linear regression for continuous variables, controlling for age and sex. For determining risk factors for chronic opioid use, univariate logistic regression was performed on variables of interest in-accordance with previous studies in the literature [24]. Factors that were significant…”
Section: Discussionmentioning
confidence: 99%
“…There also may be other variables not codified in our data which may affect postoperative opioid use, such as patients with nonspine related chronic pain. Our study is strengthened by the large sample size representative of all United States regions, and rigorous definition of chronic opioid use that requires persistent, long-term use following surgery [24,43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that psychological factors predict or are associated with opioid use (reviewed by Darnall et al) [43]. Depression preceding lumbar fusion or total joint arthroplasty is associated with increased opioid use following surgery [44,45]. Psychological factors, such as unstable mental illness, and higher depression rates than in controls, have been associated with opioid prescription and use in FM [37,41].…”
Section: Narcotic Drugs Prescription and Depressionmentioning
confidence: 99%
“…Traditional teaching on this subject has used a dualistic framework that separates issues of the mind from the body. However, a rapidly growing body of literature highlights the impact of mental health on medical outcomes such as pain, postoperative opioid use, and other chronic health conditions, including diabetes and heart disease (20). These findings reflect an increased understanding of the developmental, physiologic, and neurobiological basis of disease.…”
mentioning
confidence: 99%